Screening for osteoporosis using L1 vertebral density on abdominal CT in an Australian population. Issue 7 (July 2022) - Abbouchie, H.; Raju, N.; Lamanna, A.; Chiang, C.; Kutaiba, N.
Abstract : Aim: To assess the utility of osteoporosis screening using abdominal computed tomography (CT) versus dual-energy X-ray absorptiometry (DXA) T-scores as the reference. Materials and methods: Patients ≥30 years undergoing abdominal CT and DXA within 12 months were assessed retrospectively. Bone mineral density (BMD) was measured using axial CT attenuation at L1, correlating with DXA T-scores. Sensitivity, specificity, area under the curve (AUC), and odds ratio (OR) were calculated. Results: The study cohort comprised 407 CT–DXA pairs (58.2% women). The prevalence of osteoporosis was 11.8%. L1 density and T-score were significantly correlated in both women ( r= 0.35, p< 0.001) and men ( r= 0.15, p= 0.04). The AUC to distinguish osteoporosis from osteopenia and normal BMD was 0.64 (95% CI: 0.56–0.71). In women, a threshold of 190 HU detected T-scores ≤ –2.5 with a negative predictive value (NPV) of 94.4% (OR=4.4, p< 0.01). In the entire cohort, a threshold of 180 HU detected T-scores ≤ –2.5 with a NPV of 96.2% (OR=4.7, p< 0.01). Conclusions: CT L1 attenuation correlates with L1 DXA T-scores. Density values < 190 and 180 HU increased the probability of an osteoporosis diagnosis in Australian women and the overall cohort, respectively. Opportunistic screening for osteoporosis using abdominal CT is feasible, enabling identification of at-risk subjects for formal DXA imaging, thereby improving treatment initiation and reducing fracture risk. Highlights: CT L1 density correlates with L1 DXA T-scores. > 180 HU threshold ruled out osteoporosis/moderate osteopenia with high certainty. > 190 HU (females) decreased the probability of osteoporosis/moderate osteopaenia. Screening for osteoporosis using abdominal CT is feasible. At-risk patients can be identified for formal DXA imaging.